Effects of a regenerating matrix on the survival of birds in tropical forest fragments - Wolfe, Jared D. (2020)
Background: Vast areas of lowland neotropical forest have regenerated after initially being cleared for agricultural purposes. The ecological value of regenerating second growth to forest-dwelling birds may largely depend on the age of the forest, associated vegetative structure, and when it is capable of sustaining avian demographics similar to those found in pristine forest. Methods: To determine the influence of second growth age on bird demography, we estimated the annual survival of six central Amazonian bird species residing in pristine forest, a single 100 and a single 10 ha forest fragment, taking into consideration age of the surrounding matrix (i.e. regenerating forest adjacent to each fragment) as an explanatory variable. Results: Study species exhibited three responses: arboreal, flocking and ant-following insectivores (Willisornis poecilinotus, Thamnomanes ardesiacus and Pithys albifrons) showed declines in survival associated with fragmentation followed by an increase in survival after 5 years of matrix regeneration. Conversely, Percnostola rufifrons, a gap-specialist, showed elevated survival in response to fragmentation followed by a decline after 5 years of regeneration. Lastly, facultative flocking and frugivore species (Glyphorynchus spirurus and Dixiphia pipra, respectively) showed no response to adjacent clearing and subsequent regeneration. Conclusions: Our results in association with previous studies confirm that the value of regenerating forest surrounding habitat patches is dependent on two factors: ecological guild of the species in question and second growth age. Given the rapid increase in survival following succession, we suggest that the ecological value of young tropical forest should not be based solely on a contemporary snapshot, but rather, on the future value of mature second growth as well. © 2020 The Author(s).